Attitudes of general practice dentists in private dental clinics in Almadinah Almunawarah toward novel endodontic technologies - Mothanna AlRahabi (Ariesdue, 2016)
Objective: The purpose of this study was to evaluate the current trends and the adoption of new technologies in endodontic treatment by general practitioners in private dental clinics in Almadinah Almunawarah. Methods: A questionnaire was distributed randomly to 70 general practitioners working in private dental clinics in Almadinah Almnourah, Saudi Arabia. After one week, the questionnaires were hand-collected. Sixty-three dentists (90%) returned the questionnaire. The study was conducted between February and May 2014. Results: The results indicated that 100% of the general practitioners did not use any magnification device during root canal treatments; 11% of the respondents used digital X-ray equipment, 12.7% used an electronic apex locator, 38% used NiTi rotary instrumentation in root canal preparations, 100% did not use any adjunctive device for irrigant activation and 100% did not use new devices or techniques for root canal obturations. Conclusions: This study provides data regarding the current trends and attitudes of general practitioners in private dental clinics in Al-Madinah Al-Monawarah regarding novel technologies in endodontic treatment and reveals the gap between the new advances in endodontics and clinical practice, as well as the need to improve root canal treatment in private dental practices.